Analysis of Emissivity Effects on Subterranean Heat Transfer for Thermoelectric Power Generation - Khairun Nisa Khamil; Vikneswaran Gopala Krishnan; Azdiana Md Yusop; Mohd Faizul Mohd Sabri; Fatimah Al Zahrah Mohd Saat (International Journal of Integrated Engineering, 2026)
This research explores the impact of heat sink dimensions and surface emissivity on thermoelectric energy harvesting (TEH) system performance. Finite element models were developed to simulate a TEH system embedded in pavement. The model was partially submerged into the pavement. Only the top plate is exposed at the same level as the asphalt pavement surface to allow the harvest of thermal energy from the sunlight. The bottom plate is connected to the heat sink structure to achieve a temperature difference (?T) between the top and bottom plate. Generally, higher ?T will generate a higher thermoelectric output voltage. Hence, an analysis of the heat sink’s length and the influence of emissivity in heat transfer is conducted to improve the output of temperature difference. The study focused on optimizing heat sink length and emissivity to maximize temperature difference (?T) between the hot and cold sides of the thermoelectric generator. Simulation results guided the construction of a prototype, which was subsequently field-tested. Experimental data confirmed a significant 133% enhancement in ?T compared to previous studies, validating the positive influence of heat sink design parameters on TEH system output.